Analisis Pemetaan Potensi Ekonomi Kabupaten Nunukan - Agus Tri Darmawanto (Journal on Education, 2022)
The aims of this research are (i) to find out the economic base sector in Nunukan Regency; (ii) knowing the shift in the economic structure in Nunukan Regency (iii) classifying the pattern of economic growth structure in Nunukan Regency. This research method uses a descriptive quantitative approach. The data used in this study is secondary data from 2015-2019. The analysis used is Location Quotient (LQ) Analysis, shiftshare and class typology. The results of the LQ analysis show that the sectors that have a comparative advantage are in the 2 (two) business sectors, namely the Agriculture, Forestry and Fisheries Sector; and the Mining and Quarrying Sector. The value of provincial share, proportional shift, and differential shift, the growth value of the Total GRDP of Nunukan Regency (Dij) is positive. The typological classification of the classsen economy shows that the sectors included in quadrant I, advanced and grew rapidly (developed sectors), namely the Agriculture, Forestry Sector , and Fisheries, and, Mining and Quarrying Sector; Sectors included in quadrant II, potential or developing sectors, namely the Electricity and Gas Procurement Sector, Construction Sector, Information and Communication Sector, Financial Services and Insurance Sector, Real Estate Sector; Sectors included in Quadrant IV, relatively underdeveloped sectors, namely, Manufacturing Industry Sector, Water Procurement Sector, Waste, Waste and Recycling Management, Wholesale and Retail Trade Sector, Car and Motorcycle Repair, Transportation and Warehousing Sector, Sector Provision of Accommodation and Food and Drink, Company Services Sector, Government Administration Sector, Defense and Compulsory Social Security, Education Services Sector, Health Services and Social Activities Sector and other Service Sector. Then, in sector II, there are no sectors included in quadrant II.